Infant mental health home visiting: intervention dosage and therapist experience interact to support improvements in maternal reflective functioning. Issue 1 (2nd January 2022) - Stacks, Ann M.; Jester, Jennifer M.; Wong, Kristyn; Huth-Bocks, Alissa; Brophy-Herb, Holly; Lawler, Jamie; Riggs, Jessica; Ribaudo, Julie; Muzik, Maria; Rosenblum, Katherine L.
ABSTRACT: This study examined changes in parental reflective functioning (PRF) among mothers enrolled in Infant Mental Health-Home Visiting (IMH-HV) and explored whether parental risk, treatment dosage or therapist experience predicted change in PRF. Participants included 75 mothers and their children who were enrolled in IMH-HV delivered by Community Mental Health therapists. Results indicated significant improvements in PRF from baseline to 12-months. Maternal demographic and psychosocial risk, therapist experience and treatment dosage were not directly associated with changes in PRF. However, Mothers who received more treatment sessions from therapists with six or more years of experience demonstrated the greatest improvements in PRF, while mothers who received more treatment sessions from therapists who had been practicing IMH for less than 15 months showed a decline in PRF. Therapists working with very high-risk families may need specific training and ongoing reflective supervision over a period of years to promote improvement in PRF.